Internet use and leisure time physical activity of adults – A nationwide survey. (July 2016) - Zach, Sima; Lissitsa, Sabina
Abstract: We examined the relationships between physical activity and Internet use habits, using the Theory of Planned Behavior (TPB) and the Health Action Process Approach (HAPA) model as a framework. The purpose was to examine how Internet access, digital use, and time spent online correlate with the odds of engaging in three types of PA: strenuous, moderate, and muscle-strengthening Data relied on the Annual Social Survey conducted by Israel's Central Bureau of Statistics in 2010, with 6035 participants aged 20–65. Logistic regressions revealed that the odds of engaging versus not engaging in three types of physical activity were higher among Internet users compared to non-users. The odds of engaging versus not engaging in strenuous physical activity were higher among those who used the Internet for studying, social media, and downloading; in strengthening muscles were higher among those who used the Internet for seeking information and social media; and in moderate physical activity were higher among those who used the Internet for studying, compared to non-users. We suggest that the measured digital uses represent intention and action plans similar in their determinants to being physically active. Health care decision makers should increase availability of information on the Internet regarding a healthy lifestyle, concentrating on leisure-time physical activity habits. Highlights: Engagement in three types of PA was higher among Internet users than non-users. Digital use stems from the intention to make plans for participating in PA, as described in the Theory of Planned Behavior. Participation in PA was higher among those engaging in digital uses for studying, social media, and seeking information.